Konektivitas Pelabuhan Dan Pembangunan Ekonomi Daerah Provinsi Maluku Utara - Yetty Yetty; Abdurrahman Senuk; Chairullah Amin (JFRES Journal of Fiscal and Regional Economy Studies, 2019)
The local development approach based on islands is different with the developing of land area. The natural limitations possessed by the islands region that constrained by some characteristics such as isolation, smallness, boundless, and fragmentation. The study analyzes the impact of port connectivity to the local economic development by taking the case in the island province (North Maluku) in east Indonesia. The analysis method using the panel data model of 9 residences in period 2010-2016 in which the indicators that used are GDP, roadway, port throughput, economic density, and also container port, sea-tollway as the dummy variables. According to the common effect, model shows that all independent variables have a significant influence on the GDP except roadway. While based on Hausman test suggest that random effect model is more appropriated than FEM of which the result shows that container port and sea-tollway have not a significant impact on the GDP. These results implied that the policy of port connectivity within sea-tollway is not effective to improve the local economic development in particular in the islands based on region.